2021
DOI: 10.3389/fpsyg.2021.609893
|View full text |Cite
|
Sign up to set email alerts
|

Using the Health Belief Model to Understand Age Differences in Perceptions and Responses to the COVID-19 Pandemic

Abstract: COVID-19 severity and mortality risk are greater for older adults whereas economic impact is deeper for younger adults. Using the Health Belief Model (HBM) as a framework, this study used a web-based survey to examine how perceived COVID-19 susceptibility and severity and perceived efficacy of recommended health behaviors varied by age group and were related to the adoption of health behaviors. Proportional odds logistic regression was used to examine the relationship between age group and perceived COVID-19 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 53 publications
(62 reference statements)
5
31
0
Order By: Relevance
“…Prior cross-sectional reports revealed that good knowledge was significantly and positively correlated with practice against the COVID-19 transmission (Bechard et al, 2021;Muslih et al, 2021). It is in line with another study; approximately 52.9% of the individuals had positive knowledge regarding COVID-19 among Ethiopian citizens (Shewasinad Yehualashet et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Prior cross-sectional reports revealed that good knowledge was significantly and positively correlated with practice against the COVID-19 transmission (Bechard et al, 2021;Muslih et al, 2021). It is in line with another study; approximately 52.9% of the individuals had positive knowledge regarding COVID-19 among Ethiopian citizens (Shewasinad Yehualashet et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…This situation is in line with the previous literature established that inadequate health practices among Indonesian citizens (Rias et al, 2020) or low public behaviors of citizens regarding the COVID-19 pandemic (Jose et al, 2021), complicating efforts to prevent the spread of this pandemic. Consequently, the containment of the COVID-19 pandemic must continue to rely on personal health behaviors control to decline the exposure (Bechard et al, 2021;Jose et al, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in perception, as well as the fear of coronavirus disease, among different age groups, have been the subject of a significant number of theoretical and empirical studies [ 65 , 66 , 67 ], with a consensus that elderly members of the population are one of the most vulnerable risk groups in society [ 68 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the perceived risk of death from COVID-19 increases with age (e.g., mortality risk), but the perceived risk of being infected decreases with age as does the perceived risk of running out of money [ 4 , 5 ]. It is unclear how these risk perceptions combine to affect mitigation behaviors, particularly in older adults, although structural equation modeling suggests that the perceived effectiveness of mitigation behaviors and not perceived COVID-19 risks predicts mitigation behaviors [ 6 ].…”
Section: Introductionmentioning
confidence: 99%